Effect of acidic solutions on the microhardness of dentin and set OrthoMTA and their cytotoxicity on murine macrophage - Soram Oh; Hiran Perinpanayagam; Yoon Lee; Jae-Won Kum; Yeon-Jee Yoo; Sang-Min Lim; Seok Woo Chang; Won-Jun Shon; Woocheol Lee; Seung-Ho Baek; Kee-Yeon Kum (Restorative Dentistry & Endodontics, 2016)
Objectives To evaluate the effects of three acids on the microhardness of set mineral trioxide aggregate (MTA) and root dentin, and cytotoxicity on murine macrophage.